Hematology and blood biochemistry of young healthy broad-snouted caimans (Caiman latirostris) - Zayas, Marcelo Alejandro (2011)
Caiman latirostris (Broad-Snouted Caiman) is widely distributed in wetlands and rivers of South America. Hematological and blood chemistry reference values are necessary for detecting the effects of environmental, infectious, parasitic, or toxicological stress on C. latirostris health. Peripheral blood samples were obtained from 24 healthy 6- to 18-month-old caimans. Blood cell dimensions and cytochemistry profiles were described; and reference intervals for hematological parameters, enzyme activities, and clinical analytes were established. Based on the caiman mass frequency distribution, two classes were distinguished: 125900 g and 9013,100 g. Although an overlap in age ranges was observed, total length and snoutvent length range values from both mass classes differed. This finding is particularly useful because, in the wild, caiman age is unknown, whereas growth parameters can be easily recorded. Caiman blood cells exhibited morphological features similar to those of other reptiles, with lymphocytes being the most numerous type of leukocytes. Significant positive correlations between mass and hemoglobin concentration, hematocrit, red blood cell, and white blood cell counts were observed. Neither sex nor age was associated with differences in these parameters. Analysis of blood chemistry values found in this study was done by comparing with values reported for related species. Both similarities and discrepancies with values from other crocodiles are discussed. This study provides baseline information from healthy juvenile caimans to which subsequent measurements can be compared. These data will aid in the medical management of caiman farms, zoo conservation programs, and field studies.